SoxC transcription factors are required for neuronal differentiation in adult hippocampal neurogenesis. - Wegner, Michael; Sock, Elisabeth; Lie, Dieter Chichung; et al. (Journal of Neuroscience, 2012)
Neural stem cells (NSCs) generate new hippocampal dentate granule neurons throughout adulthood. The genetic programs controlling neuronal differentiation of adult NSCs are only poorly understood. Here we show that, in the adult mouse hippocampus, expression of the SoxC transcription factors Sox4 and Sox11 is initiated around the time of neuronal commitment of adult NSCs and is maintained in immature neurons. Overexpression of Sox4 and Sox11 strongly promotes in vitro neurogenesis from adult NSCs, whereas ablation of Sox4/Sox11 prevents in vitro and in vivo neurogenesis from adult NSCs. Moreover, we demonstrate that SoxC transcription factors target the promoters of genes that are induced on neuronal differentiation of adult NSCs. Finally, we show that reprogramming of astroglia into neurons is dependent on the presence of SoxC factors. These data identify SoxC proteins as essential contributors to the genetic network controlling neuronal differentiation in adult neurogenesis and neuronal reprogramming of somatic cells. © 2012 the authors.
UnivIS-Import:2015-03-09:Pub.2012.med.IB.LPCIPDBI.soxctr